The Immunosuppressant Fingolimod (FTY720) for the Treatment of Mechanical Force-Induced Abnormal Scars - Masayo Aoki; Akatsuki Kondo; Noriko Matsunaga; Azusa Honda; Yuri Okubo; Kazuaki Takabe; Rei Ogawa (Journal of Immunology Research)
Aim. Abnormal scars such as hypertrophic scars (HSs) and keloids are excessively growing scars that exhibit chronic inflammation and capillary vasculogenesis. The lipid mediator sphingosine-1-phosphate (S1P) is important in inflammatory cell recruitment and angiogenesis. Fingolimod (FTY720) is an analog of S1P and thus functionally antagonizes S1P receptors and inhibits the enzyme that produces S1P. We examined the effects of topical FTY720 injections on mechanical force-induced HS progression. Methods. Mechanical force-induced HSs were generated in C57BL6/J mice by suturing a dorsal incision and applying a stretching device on Days 6, 8, 10, and 12. On Days 8, 10, and 12, intracutaneous FTY720 (10 μM) or control vehicle injections were performed. On Day 14, scar tissues and blood were procured and subjected to histology and flow cytometry. Results. Flow cytometry showed that FTY720 decreased the frequencies of macrophages with M2 predominance in the scars but had no effect on total, CD4+, or CD8a+ T cell frequencies. FTY720 also decreased the vascular endothelial cell frequencies in the scar along with the microvessels, as determined by immunohistochemistry. Compared to the vehicles, FTY720 treatment significantly reduced the gross scar area and the cross-sectional scar area on histology. On the other hand, FTY720 tended to reduce white blood cells and significantly reduced the lymphocyte frequencies in the blood. Conclusion. Topical FTY720 induces M2 predominance and impairs angiogenesis. Therefore, its local immunosuppressive mechanisms differ from those of conventional immunosuppressive agents. Topical FTY720 can be a novel therapeutic option for abnormal scars that are difficult to control with corticosteroids. Its lymphocytopenic effects may be limited by careful optimization of the treatment regimen.